2005
DOI: 10.1074/jbc.m501159200
|View full text |Cite
|
Sign up to set email alerts
|

Stearoyl-CoA Desaturase Is Involved in the Control of Proliferation,Anchorage-independent Growth, and Survival in Human TransformedCells

Abstract: Saturated and monounsaturated fatty acids are the most abundant fatty acid species in mammalian organisms, and their distribution is regulated by stearoyl-CoA desaturase, the enzyme that converts saturated into monounsaturated fatty acids. A positive correlation between high monounsaturated fatty acid levels and neoplastic transformation has been reported, but little is still known about the regulation of stearoyl-CoA desaturase in cell proliferation and apoptosis, as well as in cancer development. Here we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
160
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(178 citation statements)
references
References 42 publications
14
160
0
3
Order By: Relevance
“…Although our findings of a protective role of SCD1 are consistent with data on other cell types [17,18,38], some authors [29] have suggested that elevated skeletal muscle SCD1 expression contributes to abnormal lipid metabolism and the aetiology of obesity. In this previous study [29], SCD1 overexpression decreased fatty acid oxidation and increased triacylglycerol synthesis.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Although our findings of a protective role of SCD1 are consistent with data on other cell types [17,18,38], some authors [29] have suggested that elevated skeletal muscle SCD1 expression contributes to abnormal lipid metabolism and the aetiology of obesity. In this previous study [29], SCD1 overexpression decreased fatty acid oxidation and increased triacylglycerol synthesis.…”
Section: Discussionsupporting
confidence: 81%
“…In this previous study [29], SCD1 overexpression decreased fatty acid oxidation and increased triacylglycerol synthesis. While our data largely support these observations, triacylglycerol accumulation per se is unlikely to cause insulin resistance [39] or lipotoxicity [17,18,38], and in fact may provide protection by providing a reservoir for the deposition of other fatty acyl-CoA metabolites. Importantly, our data add to these previous observations and indicate that triacylglycerol accumulation in SCD1-overexpressing cells protects cells from DAG and ceramide accumulation.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Indeed, Moore and others speculated that the down-regulation of SCD cDNA in prostate carcinoma may be due to: a) the need of the cancer cell to increase the levels of palmitate which can be done by decreasing SCD activity, b) eliminate the SCD-induced down-regulation of lipid membrane rafts and c) down-regulate susceptibility of tumor cells containing more unsaturated fatty acids to TNF-induced free radical attack [113]. Nevertheless, knockdown of human SCD in transformed human fibroblasts resulted in decreased oleic acid synthesis, lowered desaturation index profiles of the main polar lipids phosphatidylcholine and phosphatidylethanolamine, and decreased de novo synthesis of 14 C-labeled phospholipids, cholesterol and cholesterol esters, free fatty acids and triacylglycerols [114]. Interestingly, there was an inhibition in cellular proliferation and anchorage-independent growth in the SCD knockdown cells [114].…”
Section: Pancreatic Cancer -Insights Into Molecular Mechanisms and Nomentioning
confidence: 99%